Synovial sarcomas: A single surgeon experience of 130 cases. Issue 4 (7th June 2022) - Andreani, Lorenzo; Ipponi, Edoardo; Mani, Olimpia; Bayon, Ginevra; Ruinato, Alfio Damiano; Cosseddu, Fabio; D'Arienzo, Antonio; Capanna, Rodolfo
Abstract: Background: Synovial sarcoma is a rare malignant tumor that generally requires a multidisciplinary therapeutic approach. In this study we report the experience of a single surgeon, evaluating surgical and oncological outcomes of the cases he treated through his 30 years carrier. Methods: We enrolled patients treated surgically between 1988 and 2018. Surgical and medical treatments, as well as surgical and oncological results, were investigated. Results: One hundred and thirty cases were included. Surgical resection was carried out achieving wide margins in 90% of the cases. At their latest follow‐up, 76 patients were continuously disease free, 16 were no evidence of disease, and other 16 were alive with disease. Twenty cases were dead of disease and two dead of other causes. Twenty‐five patients (19%) had local recurrence of synovial sarcoma through their postoperative intercourse. Thirty‐seven patients (28%) were diagnosed with at least a metastasis during their follow‐up. The global survival of our population, at each patient's latest follow‐up, was 82%. Cases with tumor size above 5 cm had a significantly higher risk to develop metastasis ( p  = 0.002). Conclusions: Synovial sarcoma is a threatening disease and represents a challenge for oncological physicians and surgeons. Early diagnosis and multidisciplinary approach are mandatory to limit the spread of synovial sarcomas, maximizing the effectiveness of surgery and the other treatments.